2021
DOI: 10.1101/2021.03.30.437696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheC. elegansPTCHD homolog PTR-4 is required for proper organization of the pre-cuticular apical extracellular matrix

Abstract: The Patched-related (PTR) superfamily of transmembrane proteins can transport lipids or other hydrophobic molecules across cell membranes. While the hedgehog receptor Patched has been intensively studied, much less is known about the biological roles of other PTR or Patched domain (PTCHD) family members. C. elegans has a large number of PTR/PTCHD proteins, despite lacking a canonical hedgehog pathway. Here, we show that PTR-4 promotes the assembly of the pre-cuticle apical extracellular matrix (aECM), a transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Catillo et al reported that PTC-3, a C. elegans patched homolog, regulates lipid homeostasis and controls cellular cholesterol levels by acting as a cholesterol transporter [41]. Patched receptors share homology with bacterial RND transporters, and PTR-4, in particular, may act as a transporter of hydrophobic molecules, suggesting that patched/PTR proteins are transmembrane pumps for hydrophobic cargos [55]. PTR-23 might also be a lipid transporter.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Catillo et al reported that PTC-3, a C. elegans patched homolog, regulates lipid homeostasis and controls cellular cholesterol levels by acting as a cholesterol transporter [41]. Patched receptors share homology with bacterial RND transporters, and PTR-4, in particular, may act as a transporter of hydrophobic molecules, suggesting that patched/PTR proteins are transmembrane pumps for hydrophobic cargos [55]. PTR-23 might also be a lipid transporter.…”
Section: Plos Geneticsmentioning
confidence: 99%